Disruption of the Legal Profession: A Manifestation of the Ius Constituendum Principle in the Digital Era of Society 5.0 (Open Society Conference, 2025)
The legal profession is an honorable profession (officium nobile) that in carrying out its profession is under the protection of law, statutory regulations, and a code of ethics. Free and independent and not bound by a biocratic hierarchy. Given this reality, sometimes an advocate abuses his professional function, so that in society there is a perception that the legal profession defends the wrong and the work of the legal profession is not halal because the defense of the blind can reverse the state of the legal profession that will be associated with the digitalization era, where technological developments directly impact law firms, courts, police, prosecutors and other law enforcement agencies that will increasingly need many legal information engineers. It is evident in the presence of IT experts who also understand the law, which is expected to anticipate the potential negative impacts of electronic and internet use. Such expertise is also important for law enforcement institutions where they must be able to provide legal services that can help the public, the government and legislative bodies as regulators to see from a different perspective on developments in the world of law enforcement. Therefore, a joint effort is needed from all parties to seize opportunities and overcome these challenges. With strong collaboration and commitment, digital transformation can bring positive change to the legal world and improve the quality of legal services for the public. Disruption threatens the established legal profession, such as law firms, notaries, and courts. While previously the law seemed complicated for many laypeople, requiring legal counsel for those dealing with it, now artificial intelligence is available to solve various legal issues, eliminating the need for consultations with law firms.